Recurrent Surgical Site Infections in the Spine After Treatment With the Vacuum-assisted Closure (VAC) System. Issue 8 (October 2018) - Alcala-Marquez, Christopher; Torrealba, Rubén; Mehbod, Amir A.; Dawson, John M.; Dressel, Thomas D.; Transfeldt, Ensor E.
Abstract : Study Design: This study retrospectively reviewed recurrences of surgical site infections (SSI) in spinal patients treated with vacuum-assisted closure (VAC) technology. Objective: Identify patient and treatment factors associated with recurrence of SSI after VAC treatment. Summary of Background Data: Patients treated with VAC can achieve healing of deep spine wound infections; however, some patients develop a recurrent infection. Risk factors associated with a recurrence have not been identified. Materials and Methods: One hundred and eleven patients with SSI after spine surgery from 2002 to 2010 were studied. They had been treated with irrigation and debridement, placement of VAC, and IV antibiotics. They subsequently were taken to surgery for primary closure of their wound. Patients with SSI who healed after the initial infection treatment were compared with patients who experienced recurrence. Patient and treatment factors that were studied included smoking status, body mass index, obesity status, diagnosis of diabetes, fusion surgery, methicillin-resistant Staphylococcus aureus, or polybacteria infection, number of irrigation and debridement treatments before closure, duration of IV antibiotic treatment, and duration of treatment time with VAC. Patients with SSI who healed after the initial treatment were compared with patients who experienced recurrence. Results: Fourteen patients had at least one recurrence of wound infection. None of the patient or treatment factors was associated with the recurrence of a SSI. Conclusions: Among spine surgery patients with a SSI treated with the VAC system, those factors which predispose a patient to develop a recurrent SSI remain unknown. Level of Study: Level IV.